Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/lsm.23400
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐Mechanical Fractional Injury Therapy for Facial Skin Rejuvenation in Skin Types II to V: A Retrospective Double‐Center Chart Review

Abstract: Background and Objectives: Thermo-mechanical fractional injury (TMFI) therapy (Tixel®; Novoxel®, Netanya, Israel) is an innovative technology. Along with its drug delivery enhancement features, it is widely used for facial skin rejuvenation. Our study explores the beneficial effect of the Tixel® on the different features of facial skin rejuvenation along with patients′ satisfaction rate, aiming to suggest practical recommendations for an optimal aesthetic result. Study Design/Materials and Methods: A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…It has been previously shown that pulse durations around 6 milliseconds are used for drug delivery and those greater than 10 milliseconds are used for rejuvenation; common settings for rejuvenation are 12-14 milliseconds. 11,25,26 As the periorbital region is a sensitive area, coordinating treatment at two centers in different countries with diverse populations warranted more conservative treatment parameters. The depth was chosen based on the depth of the periorbital skin to the reach the papillary dermis ~300 µm (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been previously shown that pulse durations around 6 milliseconds are used for drug delivery and those greater than 10 milliseconds are used for rejuvenation; common settings for rejuvenation are 12-14 milliseconds. 11,25,26 As the periorbital region is a sensitive area, coordinating treatment at two centers in different countries with diverse populations warranted more conservative treatment parameters. The depth was chosen based on the depth of the periorbital skin to the reach the papillary dermis ~300 µm (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…TMFI technology is an excellent modality for drug delivery owing to its formation of micronsized wells in the epidermis lined by a thin rim of coagulation. 11,[27][28][29] As wrinkling in the periorbital region is exacerbated by constant contraction of the orbicularis oculi muscles with facial expression, the use of TMFI technology to deliver botulinum toxin may achieve a more profound improvement, by both diminishing muscle contraction and stimulating collagen production and remodeling in a region where the skin is thinnest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations